The influence of inspiratory and expiratory muscle training upon rowing performance - Griffiths, L. A.; McConnel, A. K. (European Journal of Applied Physiology, 2007)
We investigated the effect of 4 week of inspiratory (IMT) or expiratory muscle training (EMT), as well as the effect of a subsequent 6 week period of combined IMT/EMT on rowing performance in club-level oarsmen. Seventeen male rowers were allocated to either an IMT (n = 10) or EMT (n = 7) group. The groups underwent a 4 week IMT or EMT program; after interim testing, both groups subsequently performed a 6 week program of combined IMT/EMT. Exercise performance and physiological responses to exercise were measured at 4 and 10 week during an incremental rowing ergometer `step-test` and a 6 min all-out (6MAO) effort. Pressure threshold respiratory muscle training was undertaken at the 30 repetition maximum load (~50% of the peak inspiratory and expiratory mouth pressure, P Imax or P Emax, respectively). P Imax increased during the IMT phase of the training in the IMT group (26%, P < 0.001) and was accompanied by an improvement in mean power during the 6MAO (2.7%, P = 0.015). Despite an increase in P Emax by the end of the intervention (31%, P = 0.03), the EMT group showed no significant changes in any performance parameters during either the `step-test` or 6MAO. There were no significant changes in breathing pattern or the metabolic response to the 6MAO test in either group, but the IMT group showed a small decrease in HR (2-5%, P = 0.001). We conclude that there were no significant additional changes following combined IMT/EMT. IMT improved rowing performance, but EMT and subsequent combined IMT/EMT did not.